RANCANG BANGUN E-LEARNING UNTUK KOMPONEN PESAWAT TERBANG ( STUDI KASUS DI STTA YOGYAKARTA) - Gilang Wiratmaja; Hero Wintolo; Nurcahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2016)
At this time need to develop the education system urgent to do. Various concepts and new techniques in teaching and learning has been developed to replace conventional teaching methods in class. this was due to a global computer network found. One method of teaching that is thrive at the present time is an e–learning. E-learning can help teachers to give subject matter without located in class by using the internet, it can maximize the limited time in class learning. The methodology used in the preparation of this study is study literature while the phase of system development using web engineering. To design these applications use several stages starting from data flow diagram (DFD), flowchart system, design table, relation table and design interface. After the e-learning application is completed and tested to 30 respondent sthrough the results questionnaire then got the result that the applications facilitate learning activities between faculty and students so as to improve the quality of learning. Significant results of the test by 30 respondents, this application are users friendly, stable and smooth. Then interactivity of learning via e-learning system can help mastery of e-learning.